Economies of Scale of General Cargo Ships - Jansson, Jan Owen; Shneerson, Dan (The Review of Economics and Statistics, 1978)
ECONOMIES of ship size have in recent years been held up as the salient feature in modern shipping. The size of ships has been increasing very rapidly, leading many students of shipping to believe that no limit exists for the optimal size and that there are only exogenous constraints, such as restricted port depths, etc. This paper presents a model of production and costs of the ship and empirical estimates of both economies and diseconomies to ship size. The approach taken in specifying production and cost relationships is the engineering approach, which seems particularly suitable because of certain basic technological (geometric, in fact) principles. The values of the parameters derived through these technological relationships are confirmed by an empirical estimate of data on production and costs. Unlike industrial plants where plant size is indicative of output capacity, for ships a distinction must be made between two output capacities-the handling capacity and the hauling capacity. Our main conclusion is that while there are economies of ship size in the hauling operations, there are diseconomies to size in the handling operation. The latter factor is the main check on ship size and explains the existence of a wide range of ship sizes currently in service.